Schott's sporting, gaming & idling miscellany - Schott, Ben 1974- (London Bloomsbury Publishing Plc, 2004)
Presents a collection of miscellaneous facts on various sports and sports-related topics, including what the different colors of karate belts mean, why surfing is the "sport of kings," and which athletes wore the "Got Milk" moustache.
Includes index.
Keywords: Sports -- Miscellanea